ANALISIS PENGARUH POLA PENGGUNAAN LAHAN TERHADAP HARGA LAHAN KORIDOR JALAN DARMO SURABAYA SEBAGAI KAWASAN PRESERVASI - Caprityan, Revin; Dwi Rohmadiani, Linda; Sugito, Sugito (Fakultas Teknik , Universitas PGRI Adi Buana Surabaya, 2014)
Road Corridor Darmo Surabaya is one of the areas that have historical value in the past. Having old buildings are still original and its location in the middle of the city with such a high accessibility makes Darmo Road Corridor has its own economic value. Various land uses such as residential, office, trade, services, social, cultural and so on. Corridor which has the highest land prices in Surabaya related to land use, the price of land and buildings located along the corridorpreservation Highway Darmo. The result of the analysis is the pattern of land use and preservation of buildings located along the road corridor Darmo significantly affect the price of the land because of strong historical value with less kirasan prices there are about more than 25 million dollars for the building of colonial and getting down to about 10 million dollars for the building has undergone many reforms.